Homeostatic calcium fluxes, ER calcium release, SOCE, and calcium oscillations in cultured astrocytes are interlinked by a small calcium toolkit. (January 2022) - Schulte, Annemarie; Bieniussa, Linda; Gupta, Rohini; Samtleben, Samira; Bischler, Thorsten; Doering, Kristina; Sodmann, Philipp; Rittner, Heike; Blum, Robert
Highlights: Dual-color calcium imaging (ER-cytosol) describes new features of homeostatic calcium fluxes. Calcium homeostasis is based on a small calcium toolkit. IP3 -induced -, Ca 2+ -induced calcium release, and calcium oscillations are physiologically interlinked. Calcium oscillations are shaped by circular spatiotemporal signal components. Abstract: How homeostatic ER calcium fluxes shape cellular calcium signals is still poorly understood. Here we used dual-color calcium imaging (ER-cytosol) and transcriptome analysis to link candidates of the calcium toolkit of astrocytes with homeostatic calcium signals. We found molecular and pharmacological evidence that P/Q-type channel Cacna1a contributes to depolarization-dependent calcium entry in astrocytes. For stimulated ER calcium release, the cells express the phospholipase Cb3, IP3 receptors Itpr1 and Itpr2, but no ryanodine receptors (Ryr1–3). After IP3 -induced calcium release, Stim1/2 – Orai1/2/3 most likely mediate SOCE. The Serca2 ( Atp2a2 ) is the candidate for refilling of the ER calcium store. The cells highly express adenosine receptor Adora1a for IP3 -induced calcium release. Accordingly, adenosine induces fast ER calcium release and subsequent ER calcium oscillations. After stimulation, calcium refilling of the ER depends on extracellular calcium. In response to SOCE, astrocytes show calcium-induced calcium release, notably even after ER calcium was depleted by extracellular calcium removal in unstimulated cells. In contrast, spontaneous ER-cytosol calcium oscillations were not fully dependent on extracellular calcium, as ER calcium oscillations could persist over minutes in calcium-free solution. Additionally, cell-autonomous calcium oscillations show a second-long spatial and temporal delay in the signal dynamics of ER and cytosolic calcium. Our data reveal a rather strong contribution of homeostatic calcium fluxes in shaping IP3 -induced and calcium-induced calcium release as well as spatiotemporal components of intracellular calcium oscillations. Graphical abstract: Image, graphical abstract